Preclinical Study of ZSP1273, a Potent Antiviral Inhibitor of Cap Binding to the PB2 Subunit of Influenza A Polymerase - Xiaoxin Chen; Qinhai Ma; Manyu Zhao; Yuqin Yao; Qianru Zhang; Miao Liu; Zifeng Yang; Wenbin Deng (MDPI AG, 2023)
The influenza A virus is highly contagious and often causes global pandemics. The prevalence of strains of the influenza A virus that are resistant to approved drugs is a huge challenge for the current clinical treatment of influenza A. RNA polymerase is a pivotal enzyme in the replication of the influenza A virus, and it is a promising target for anti-influenza A therapies. In this paper, we report a novel and potent anti-influenza-A-virus inhibitor, ZSP1273, targeting the influenza A virus RNA polymerase, especially for multidrug-resistant strains. The inhibitory activity of ZSP1273 on RNA polymerase activity was 0.562 ± 0.116 nM (IC50 value), which was better than that of the clinical candidate compound VX-787 with the same target. In vitro, the EC50 values of ZSP1273 on normal influenza A virus strains (i.e., H1N1 and H3N2) varied from 0.01 nM to 0.063 nM, which were better than those of the licensed drug oseltamivir. Moreover, oseltamivir-resistant strains, baloxavir-resistant strains, and highly pathogenic avian influenza strains were also sensitive to ZSP1273. In vivo, ZSP1273 effectively reduced influenza A virus titers in a dose-dependent manner in a murine model and maintained a high survival rate in mice. In addition, the inhibitory activity of ZSP1273 on influenza A virus infection was also observed in a ferret model. Pharmacokinetic studies showed the favorable pharmacokinetic characteristics of ZSP1273 in mice, rats, and beagle dogs after single-dose and continuous multiple-dose administration. In conclusion, ZSP1273 is a highly effective anti-influenza A virus replication inhibitor, especially against multidrug-resistant strains. ZSP1273 is currently being studied in phase III clinical trials.